Changes in food quality and habits in urban Ghana: evidence from a mixed-methods study - Sandra Boatemaa Kushitor; Lydia Okoibhole; Megan Vaughan; Kafui Adjaye-Gbewonyo; Irene Akwo Kretchy; Olutobi Adekunle Sanuade; Leonard Baatiema; Samuel Amon; Kojo Mensah Sedzro; Mawuli Komla Kushitor; Akanksha Abhay Marphatia; Emeline Rougeaux; et al. (BMC Public Health)
Abstract Background Globally, diets are changing from good quality to limited nutrition. However, an in-depth analysis of the nature of the changes is under-researched. This study examined past and current food consumption, acquisition, and preparation habits of urban poor residents in Accra, Ghana. Methods Data from the Contextual Awareness Response and Evaluation: Diabetes in Ghana project was used. The Food Group Diversity Score, NCD-Risk and NCD-Protect scores were calculated using the Diet Quality Questionnaire and analysed using means and crosstabulations with the estimation of the 95% confidence intervals (n = 854). Focus group discussions were held to discuss current and past food habits, and data were analysed thematically (n = 30). The qualitative and quantitative data were integrated during the analysis. Results From the early 1950s to the 1980s, the community consumed more traditional homemade meals made from cassava, corn and plantains (such as fufu, kenkey, kokonte and ampesi). Currently, the community consume these traditional meals in addition to foods considered modern, such as instant noodles (6%), milk (19%), rice (67%), sugar-sweetened beverages (21%), and Milo (21%). Respondents, on average, ate four food groups (x̄=3.8 ± 1.5) and about half were food insecure (47%). The most frequently consumed NCD-protect foods were whole grains (63%) and other vegetables (69%). The NCD-risk items commonly consumed were deep-fried foods (23%), unprocessed red meat (22%) and sugar-sweetened beverages (21%). Conclusion Respondents reported a shift from home cooking and communal meals toward eating out-of-home meals. The current dietary habits reflect a hybrid of modern foods with traditional foods. Food insecurity is high, and their diets provide little protection against chronic non-communicable diseases. This limits opportunities to move towards healthy diets and improved health outcomes as envisioned in the Agenda 2030.